Komunikasi Bapak/Ibu Dengan Anak Perspektif Pendidikan: (Tinjauan Tematik Ayat-Ayat Al Qur'an) - Nurul Hidayati (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
This article talks about communication between parens and children in educational perspective inspired by verses of tho Qur’an that tells the story of communication between father and child, that is 9 pairs of communication betwen mother and child and one pair of communication between mother and child. The dominant number does not mean the father has more influence on the education of the child than the mother but it is anak call for the father who generally hands over the household affairs to the mother including the education of the child. On the hand, the Qur’an has a good reason when presenting a story with a male figure, because men are more respected than women, especiallyin the time of the descent of the Qur’an. The education values we can observe from the ten pairs of communication stories in the Qur’an are parent must be good at processing and making communication with children as a field to transfer educational materials. How parents are able to provide a lightweight education without feeling burdened and heavy in the soul of the child, but embedded in their heart andcan be a reference in every problemthey face.